Phygital Experience Platform for Textile Exhibitions in Small Local Museums - Supaporn Chai-Arayalert; Supattra Puttinaovarat; Wanida Saetang (Heritage)
This study introduces a comprehensive phygital framework tailored for small local museums, addressing the unique challenges of textile exhibitions. By seamlessly integrating physical artifacts with advanced digital tools through a user-centered design–thinking approach, the platform transforms traditional museum visits into hybrid experiences. The research addresses challenges faced by small museums, such as limited interactivity, static information presentation, and resource constraints. The findings demonstrate that the phygital platform significantly enhances visitor satisfaction, usability, and engagement. Features like mobile applications, chatbots, and gamification foster dynamic interactions, increasing interest in historical textile collections. The evaluation highlights positive impacts on visitor learning and accessibility, with high usability scores and favorable feedback confirming the platform’s success. By bridging physical and digital realms, the platform empowers small local museums to modernize their exhibition experience offerings while preserving their authenticity and cultural significance. This study contributes to the growing literature on phygital strategies in museum contexts, offering practical recommendations for implementing such platforms in resource-constrained settings. The findings underscore the potential of phygital approaches to foster deeper connections with cultural heritage, ensure broader accessibility, and support sustainable visitor engagement.